Os salões e as bienais na década de 1960: itinerâncias entre os circuitos artísticos na conformação de uma história da arte no Brasil - Nelyane Gonçalves Santos (2020)
The research aimed to develop a narrative of art history in Brazil of the 1960s based on the itinerancy between the artists and critics participating in the Salons and Biennials. The events selected for the study were: Parana Salons of Fine Arts; Municipal Salons of Fine Arts of Belo Horizonte-MG; Salons of Modern Art of the Federal District; Salons of Contemporary Art of Campinas-SP, and International Biennial of São Paulo, from 1963 to 1968. With the participation of the artists, the museums and institutions promoting these events acquired and incorporated their works into their collections. Due to this procedure it is currently possible to access some of the works exhibited. Selection and award juries, mostly art critics, also circulated intensively between the Salons and Biennials. In their choices we can identify the main artistic trends in vogue at the time, which stimulated public debate among the components of art circuits. The research unfolded in the search for documentary sources in memory institutions historically related to the promotion of these events, in the analysis of sources related to the critique of the time and in the description, interpretation and analysis of the works of art that were found. Thus, it is a study that relates the historiography of art and the material culture resulting from the promotion of these events by the artistic circuits in the country. Seeking to answer the question about what is the importance of regional salons in the formation of artistic circuits in this period, it is expected that the thesis can contribute to broaden the narratives of art history in Brazil in the 1960s.